2011
DOI: 10.4103/0971-9784.83996
|View full text |Cite
|
Sign up to set email alerts
|

Intra-aortic balloon pump use does not affect the renal function in patients undergoing off pump coronary artery bypass surgery

Abstract: Renal dysfunction is known to occur during cardiac surgery. A few factors such as perioperative hypotension, use of potential nephrotoxic therapeutic agents, radio opaque contrast media in the recent past, intra-aortic balloon pump (IABP) and cardiopulmonary bypass have been blamed as the contributing factors to the causation of postoperative renal dysfunction in cardiac surgical patients. At times, in patients with renal failure and low cardiac output status, one may face the dilemma if the use of IABP is saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Muniraju et al [37] reported a prospective observational study of the use of a preoperative IABP in patients undergoing elective off-pump coronary artery bypass surgery. They found no change in serum creatinine from the baseline value of 1.10 ± 0.233 to 0.98 ± 0.363 mg/dl (p > 0.05).…”
Section: Percutaneous Devices and Renal Functionmentioning
confidence: 99%
“…Muniraju et al [37] reported a prospective observational study of the use of a preoperative IABP in patients undergoing elective off-pump coronary artery bypass surgery. They found no change in serum creatinine from the baseline value of 1.10 ± 0.233 to 0.98 ± 0.363 mg/dl (p > 0.05).…”
Section: Percutaneous Devices and Renal Functionmentioning
confidence: 99%